Sumo: cell biology - Meulmeester, Erik; Melchior, Frauke (Nature, 2008)
A protein called small ubiquitin-related modifier (SUMO) can be coupled to other proteins to control their function. This SUMOylation has been implicated in the regulation of a host of cellular processes, and is essential for the health, and even the survival, of most organisms.
Gesehen am 13.03.2023